Safety Behaviour: Commuting in Public Van in Bangkok and Vicinity - Surakan , Amaraporn; Chaiakkarakan, Napattararat (Journal of Behavioral Science for Development, 2022)
This research aims to 1) study for factors affecting safety behaviour among public van passenger in Bangkok and vicinity 2) to explain the conditions related to the safety behaviour of daily public van commuting through the perception of commuters and public van drivers. Mixed method: explanatory sequential design was conducted to collect data from 3 public van stations which are Bangkok-Chonburi route, Bangkok-Phetchaburi route and Bangkok-Nakhonnayok route. Completed data was received from 212 passengers and 45 van drivers. The data analysis is done using multiple regression analysis and content analysis. The findings reveal that 1) people’s knowledge and attitudes towards safety have impact on the safety behaviour of the commuters at 0.001 statistical significance with the predictable rate of 29%; and 2) The public van drivers revealed that public van drivers perceived severity of consequences of risk behaviour, safe-drivingbehaviour, and guidelines for basic safe-driving knowledge, however, they cannot always drive safely. For public van passenger, they perceived guildelines for public van commuting, rules for public van commuting and barriers of safe-driving behaviour. The results of this research enhance safety behaviour in commuting public van.